Juventudes secundaristas, educação, cultura e política : o fenômeno das ocupações de 2016 em Porto Alegre/RS - Ferreira, Sofia Rodrigues (2017)
This research consists of a reflection on the phenomenon of school occupations carried out by the secondary youths of the city of Porto Alegre, as well as the search to understand the effects that the phenomenon may have created in the school reality of the occupied schools. The occupations of state schools occurred from May to June of 2016. Such approach was made in order to understand the collective organizations, cultural manifestations and political negotiations developed by students throughout the school occupations period. For this purpose, I observed three schools of the metropolitan region of Porto Alegre as well as I carried out a selection of published journalistic material on the event. In order to investigate the effects caused on the school reality by the occupations, from the perspective of the students, seven young people who engaged on the occupations in their schools were interviewed. The notions of youths and youth culture supported the understanding of the phenomenon, as well as the reflection on identity issues that constitute some premises of the subject in late modernity. The importance of spaces of sociability, the exercise of negotiation and recognition of the differences in school territory as juvenile demands are some elements in the analysis and reflection of this research.